Efek Ekstrak Etanol Kulit Kayu Manis (Cinnamomum zeylanicum Blume) Terhadap Susunan Saraf Pusat Mencit Betina Putih - Helmi Arifin; Leli Sriyani; Zet Rizal (Jurnal Farmasi Higea, 2010)
Research on central nervous system stimulant activity of the ethanol extract of Cinnamomum zeylanicum Blume bark against female white mice with different levels of doses have been done. Testing done by observing the immune system by using a rotary road test, motor activity and sensory observations using automatic tool hole board, and observation of sleep and long sleep induction. Phenobarbital 50 mg / kg bw used as inducted . Preliminary trials showed that the ethanol extract of Cinnamomum zeylanicum blume with a dose of 500 mg / kg bw had an effect on the central nervous system. Whereas at the specific testing, the effect on the central nervous looks at a dose of 250 mg / kg bw, which showed a statistically significant difference compared with the control group of animals (P <0.05).